2020
DOI: 10.3390/nu12051531
|View full text |Cite
|
Sign up to set email alerts
|

The Presence of Caffeic Acid in Cerebrospinal Fluid: Evidence That Dietary Polyphenols Can Cross the Blood-Brain Barrier in Humans

Abstract: Epidemiological data indicate that a diet rich in plant polyphenols has a positive effect on brain functions, improving memory and cognition in humans. Direct activity of ingested phenolics on brain neurons may be one of plausible mechanisms explaining these data. This also suggests that some phenolics can cross the blood-brain barrier and be present in the brain or cerebrospinal fluid. We measured 12 phenolics (a combination of the solid-phase extraction technique with high-performance liquid chromatography) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(44 citation statements)
references
References 57 publications
1
43
0
Order By: Relevance
“…Interestingly, a recent study demonstrated the presence of non-endogenous caffeic acid in the human CSF. These studies confirm that plant phenolics can cross the BBB in humans and reach the neurons and microglia [42]. However, the exact mechanisms by which they may permeate the BBB are not fully understood.…”
Section: Discussionmentioning
confidence: 62%
“…Interestingly, a recent study demonstrated the presence of non-endogenous caffeic acid in the human CSF. These studies confirm that plant phenolics can cross the BBB in humans and reach the neurons and microglia [42]. However, the exact mechanisms by which they may permeate the BBB are not fully understood.…”
Section: Discussionmentioning
confidence: 62%
“…Phenolic acids have been shown to modulate different factors associated with the pathogenesis of neurodegenerative diseases, such as systemic inflammation and oxidative stress, and thus indirectly affect cognitive health [ 40 ]. As suggested by the evidence from experimental studies, specific phenolic acids and their metabolites (i.e., caffeic acid, ferulic acid) have been found in cerebrospinal fluid, suggesting that these compounds may cross the blood–brain barrier and thus directly affect brain cells [ 41 , 42 ]. Moreover, new evidence suggests that there is an interaction between dietary polyphenols and gut microbiota and their effect toward the brain [ 43 , 44 ]: it has been determined that gut microbiota composition significantly affects the bioavailability of polyphenols including phenolic acids and consequently may mediate and modulate the effect of dietary polyphenols toward cognitive health [ 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, chlorogenic acid was maintained in plasma and entered the CNS following intravenous injection in rats [52]. In a clinical study, individuals who had consumed foods containing caffeic acid showed increased caffeic acids levels in the CNS crossing the blood-brain barrier [53]. However, it remains unclear which bioactive component(s) with anti-microglial activation effects are present in the butanol fraction of EJE.…”
Section: Discussionmentioning
confidence: 99%